Fasting and postprandial levels of ghrelin, leptin and insulin in lean, obese and anorexic subjects - Korek, Emilia; Krauss, Hanna; Gibas-Dorna, Magdalena; Kupsz, Justyna; Piątek, Małgorzata; Piątek, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Ghrelin, leptin and insulin are involved in neurohormonal regulation of energetic homeostasis. Aim: We investigated the correlation between nutritional status and plasma levels of leptin, ghrelin and insulin in lean, obese and anorexic subjects. Material and methods: Nineteen obese and 18 anorexic adults were enrolled in the study. Seventeen adults with normal body mass index (BMI) served as controls. Blood samples were taken twice: before breakfast and 2 h after breakfast. Fasting and postprandial ghrelin, leptin and insulin were examined. The following correlations were estimated: between BMI and basal level of tested hormones, between insulin and ghrelin, and between insulin and leptin. The threshold level of significance was p ≤ 0.05 for all calculations. Results: Basal insulin level was lowest in anorexic patients and greatest in obese subjects. Fasting plasma ghrelin was lower in obesity and higher in anorexia as compared with the controls. Comparing with controls, fasting leptin levels were higher in obese and lower in anorexic subjects. There was positive correlation between BMI and basal leptin level in obesity. A significant postprandial increase was noted for insulin in all studied groups. Increased leptin and decreased ghrelin levels were detected 2 h after a meal in the control group. In obese patients, postprandial leptin was lower than before food intake, and fasting leptin showed positive correlation with basal insulin level. Conclusions : Basal plasma ghrelin, leptin and insulin levels differ according to nutritional status. Impaired ghrelin and leptin secretion and insulin sensitivity may be involved in the pathogenesis of eating disorders.